New Taxa For Trachomitum Woodson (Apocynaceae) in Iraq - AI- Mashhadani, A.N; Al-Ani, M.N (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study includes a morphological investigation to the plant specimens of the genus Trachomitum which assembling by one species in Iraq it is T venetum (L.) Woodson. The specimens in the Iraqi herbaria and that which is collected for the first time from new locations. After a detail and specific investigation for all the characteristic features, and according to the obvious variations between different parts of the plants we can identify the specimens of the species .T venetum into three subspecies which are subsp. armenum, subsp. scabrum and subsp. sarmatiense . The two previous subspecies were described and recorded in the first time for Iraq. There is a diagram for each taxon.